The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3389/fphar.2022.1040350
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus and its formulas as a therapeutic option for fibrotic diseases: Pharmacology and mechanisms

Abstract: Fibrosis is the abnormal deposition of extracellular matrix, characterized by accumulation of collagen and other extracellular matrix components, which causes organ dysfunction and even death. Despite advances in understanding fibrosis pathology and clinical management, there is no treatment for fibrosis that can prevent or reverse it, existing treatment options may lead to diarrhea, nausea, bleeding, anorexia, and liver toxicity. Thus, effective drugs are needed for fibrotic diseases. Traditional Chinese medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 150 publications
0
14
0
Order By: Relevance
“…The activation of the Smads pathway and its subsequent nuclear translocation are critical steps in TGF-β1-mediated fibrosis. 19 In our study, the protein expression of TGF-β1 and Smads in kidney tissues was detected via Western blot (Figure 5). When compared with db/m mice, as expected, the protein expression of TGF-β1 and Smad2/3 was significantly increased and that of Smad7 was decreased in the db/db mice (Figure 5A−C).…”
Section: ■ Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…The activation of the Smads pathway and its subsequent nuclear translocation are critical steps in TGF-β1-mediated fibrosis. 19 In our study, the protein expression of TGF-β1 and Smads in kidney tissues was detected via Western blot (Figure 5). When compared with db/m mice, as expected, the protein expression of TGF-β1 and Smad2/3 was significantly increased and that of Smad7 was decreased in the db/db mice (Figure 5A−C).…”
Section: ■ Resultsmentioning
confidence: 63%
“…The activation of the Smads pathway and its subsequent nuclear translocation are critical steps in TGF-β1-mediated fibrosis . In our study, the protein expression of TGF-β1 and Smads in kidney tissues was detected via Western blot (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Oxidation, and imbalance in oxidation, can be attributed to the fluctuations in the levels of antioxidant enzymes linked to pulmonary fibrosis, as well as ROS catalyzed by NOX2/4. Studies have revealed that white tea extract and astragalus could enhance the level of antioxidant enzymes in lung tissue, strengthen the antioxidant capacity of lung tissue, and exhibit antifibrotic properties [59].…”
Section: Oxidative Stress Responsementioning
confidence: 99%
“…It is widely utilized as an alternative treatment for immunological diseases, metabolic diseases, and liver fibrosis. [11][12][13] Astragaloside IV (AS-IV), the main active substance of Astragalus membranaceus, with the molecular formula of C 41 H 68 O 14 , can inhibit the abnormal expression of lipid synthesis-related genes, improve the ability to resist oxidative stress, reduce the degree of endoplasmic reticulum stress, decrease inflammatory response, and inhibit apoptosis. [14][15][16] AS-IV can improve liver lipid deposition in mice with NAFLD.…”
Section: Introductionmentioning
confidence: 99%